2016
DOI: 10.1249/mss.0000000000001035
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Improves Insulin Sensitivity in the Absence of Changes in Cytokines

Abstract: Purpose. The benefits of aerobic exercise training on insulin sensitivity in subjects with the metabolic syndrome (MetS) are, at least in part, associated with changes in cytokines. Recent studies identified novel cytokines (e.g. fractalkine, omentin and osteopontin) that are strongly involved in glucose homeostasis and therefore potentially contribute in the exercise-induced changes in insulin sensitivity. Therefore, we aim to examine changes in skeletal muscle RNA expression and plasma levels of novel cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 43 publications
2
12
1
Order By: Relevance
“…When focusing on the changes in maternal serum cytokines from baseline to 34th week and delivery, exercise showed a non-significant but clinically meaningful [43] association with greater IL-8 and IL-10, and lower IFN-γ and TNF-α levels in maternal serum at the 34th week; and with lower maternal IL-1β and higher maternal IL-10 at delivery.Fractalkine (CX3CL1) is a chemokine with an important role in the fetal-placental vasculature development [44] and microglial cell migration-activation [45]. When considering its role as a myokine [14], previous studies have suggested that physical exercise is not related to either fractalkine mRNA nor to protein concentrations in the general population, which is in agreement with our results [14,16,46]. However, these findings cannot be directly compared as there are no previous similar studies on fractalkine in pregnant women.Besides its pro-inflammatory role [1,3], muscle-derived IL-8 (CXCL8) can also act as an angiogenic factor during early and late gestation [15].…”
supporting
confidence: 91%
“…When focusing on the changes in maternal serum cytokines from baseline to 34th week and delivery, exercise showed a non-significant but clinically meaningful [43] association with greater IL-8 and IL-10, and lower IFN-γ and TNF-α levels in maternal serum at the 34th week; and with lower maternal IL-1β and higher maternal IL-10 at delivery.Fractalkine (CX3CL1) is a chemokine with an important role in the fetal-placental vasculature development [44] and microglial cell migration-activation [45]. When considering its role as a myokine [14], previous studies have suggested that physical exercise is not related to either fractalkine mRNA nor to protein concentrations in the general population, which is in agreement with our results [14,16,46]. However, these findings cannot be directly compared as there are no previous similar studies on fractalkine in pregnant women.Besides its pro-inflammatory role [1,3], muscle-derived IL-8 (CXCL8) can also act as an angiogenic factor during early and late gestation [15].…”
supporting
confidence: 91%
“…, ; Verheggen et al. ) involving a total of 166 subjects with a priori increased cardiovascular risk.…”
Section: Methodsmentioning
confidence: 99%
“…Smokers were also excluded. In total, we collected data from 10 endurance training studies (Walsh et al 1985Maiorana et al 2001Maiorana et al , 2002Thijssen et al 2006;Oudegeest-Sander et al 2013;Scholten et al 2014;Schreuder et al 2014Schreuder et al , 2015Verheggen et al 2016b) involving a total of 166 subjects with a priori increased cardiovascular risk.…”
Section: Participantsmentioning
confidence: 99%
“…Recent evidence have implicated that the possible role of omentin-1 in the pathophysiology of obesity and insulin resistance [8]. The omentin-1 circulating levels are inversely related to insulin resistance and are decreased in obesity, as well as type 2diabetes [9]. Ansari et al [10] newly reported decrease in omentin-1 serum level among smokers as a metabolic risk factor and as a major prognostic agent of lung cancer in these individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise training is an important non-pharmacological strategy to improve insulin sensitivity via several metabolic/physiological changes [9]. Since, regular exercise training diminishes the risk factors for metabolic diseases such as obesity, type 2diabetes, and cardiovascular disease [12], may modify circulating omentin-1 level.…”
Section: Introductionmentioning
confidence: 99%